2022
DOI: 10.1007/s43450-022-00342-x
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological Activities and Pharmacokinetics of Glycycoumarin

Abstract: Glycycoumarin is a representative coumarin compound with significant pharmacological activities isolated from Glycyrrhiza uralensis Fisch., Fabaceae. Studies have shown that glycycoumarin has many biological activities, such as anti-tumor, liver protection, antispasmodic, antibacterial, and antivirus. However, the poor solubility of glycycoumarin in water and the accompanying reactions of the phase I (hydroxylation) and II (glucuronidation) metabolism limit its druggability, which manife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…A combined analysis of differential metabolites and differential bacteria revealed a positive correlation between the abundance of Akkermansia muciniphila and glycycoumarin. Glycycoumarin, a representative coumarin compound, exhibits significant pharmacological activities, including antitumor, hepatoprotective, antispasmodic, antibacterial, and antiviral effects ( Tang et al., 2023 ). We also found a negative correlation between the abundance of Akkermansia muciniphila and the molecular substances named Ala-Lys-Asn-Glu.…”
Section: Discussionmentioning
confidence: 99%
“…A combined analysis of differential metabolites and differential bacteria revealed a positive correlation between the abundance of Akkermansia muciniphila and glycycoumarin. Glycycoumarin, a representative coumarin compound, exhibits significant pharmacological activities, including antitumor, hepatoprotective, antispasmodic, antibacterial, and antiviral effects ( Tang et al., 2023 ). We also found a negative correlation between the abundance of Akkermansia muciniphila and the molecular substances named Ala-Lys-Asn-Glu.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, Yan Zhang and Jing Wang reported that ellipticine can alleviate glucocorticoid‐induced osteoporosis in vivo by increasing osteocalcin levels and increasing bone parameters, such as bone mineral content (BMC) and bone mineral density (BMD). It also lowers the levels of bone glycoprotein (BGP), acid phosphatase (ACP), alkaline phosphatase (ALP), tartrate‐resistant acid phosphatase (TRAP), and β‐CTx [31] …”
Section: Ellipticinementioning
confidence: 99%